2018
DOI: 10.5296/ijele.v6i2.13408
|View full text |Cite
|
Sign up to set email alerts
|

Exploring EFL Teachers’ and Students’ Perceptions of Learner Autonomy in Egyptian Technical Schools

Abstract: This study aimed at exploring the perceptions of learner autonomy of 265 students and 89 EFL teachers in technical secondary schools in Egypt. Both qualitative and quantitative data were collected through student questionnaire, teacher questionnaire, and teacher interviews. The findings revealed that the participants; students and teachers, have positive views about learner autonomy in language learning. Students were generally aware of the autonomy-boosting practices and teachers" roles in fostering autonomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…He utilized semi-structured interviews and questionnaires to autonomous language learning in terms of observable activities of autonomous language learning and they used questionnaires to collect data and SPSS to analyze data. The results indicated that participants show strong beliefs of autonomous learning, but the behaviors outside class are not at such a high level Khalil and Ali (2018). examined the perceptions of LA of both EFL teachers and learners.They used questionnaires for 265 student participants, and questionnaires and interviews for teachers to collect data.…”
mentioning
confidence: 99%
“…He utilized semi-structured interviews and questionnaires to autonomous language learning in terms of observable activities of autonomous language learning and they used questionnaires to collect data and SPSS to analyze data. The results indicated that participants show strong beliefs of autonomous learning, but the behaviors outside class are not at such a high level Khalil and Ali (2018). examined the perceptions of LA of both EFL teachers and learners.They used questionnaires for 265 student participants, and questionnaires and interviews for teachers to collect data.…”
mentioning
confidence: 99%